Infanticide Cases at a Top Referral Hospital in West Java, Indonesia: Prevalence and Causes from 2019 to 2023 - Luna Oktavia Lumbantoruan; Nita Novita; Naomi Yosiati (Althea Medical Journal, 2025)
Background: Infanticide refers to the intentional killing of a newborn by the biological mother shortly after birth, which can be proven through internal and external forensic examinations. This study aimed to determine the prevalence and  causes of suspected infanticide cases at a top referral hospital in West Java, Indonesia.